2016
DOI: 10.15376/biores.11.1.2319-2333
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Wood Flour Reinforced Lignin-Epoxy Resin Composite

Abstract: A lignin-epoxy resin composite was prepared by blending lignin/wood flour with an epoxy resin and polyamine. The effects of the wood flour on the mechanical, thermal creep, and creep recovery properties, as well as the microstructure of the composite, were studied. Among the mechanical properties, the initial modulus increased with increasing content of wood flour. The glass transition temperature (Tg) decreased, and the thermal stability first decreased and then increased, as the wood flour content increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Selected References Fracture of the cellulose-based reinforcement Summerscales et al 2010;Alavi et al 2013;Fonseca-Valero et al 2015;He et al 2016 Debonding between the matrix & reinforcement Alavi et al 2013;He et al 2016;Mu et al 2018;Simao et al 2019 Debonding within agglomerates of cellulosebased reinforcements Ismail & Shafiq 2016;Lewandowska et al 2018;DiLoreto et al 2019 Large increases in strength when using compatibilizing agents George et al 2001;Fu et al 2008;Farsi 2012;Alavi et al 2013;Durmus et al 2019 The quality of bonding between a cellulosic surface and a plastic matrix material tends to be of critical importance. Gaugler et al (2019) recently showed that such bonds can be evaluated quickly and precisely by preparing sandwich-type composites.…”
Section: Type Of Mechanistic Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Selected References Fracture of the cellulose-based reinforcement Summerscales et al 2010;Alavi et al 2013;Fonseca-Valero et al 2015;He et al 2016 Debonding between the matrix & reinforcement Alavi et al 2013;He et al 2016;Mu et al 2018;Simao et al 2019 Debonding within agglomerates of cellulosebased reinforcements Ismail & Shafiq 2016;Lewandowska et al 2018;DiLoreto et al 2019 Large increases in strength when using compatibilizing agents George et al 2001;Fu et al 2008;Farsi 2012;Alavi et al 2013;Durmus et al 2019 The quality of bonding between a cellulosic surface and a plastic matrix material tends to be of critical importance. Gaugler et al (2019) recently showed that such bonds can be evaluated quickly and precisely by preparing sandwich-type composites.…”
Section: Type Of Mechanistic Evidencementioning
confidence: 99%
“…Effects of particle size were considered by He et al (2016), who studied the reinforcement of an epoxy matrix with poplar wood flour and polyamine. With decreasing size of the wood flour particles, the mechanical properties initially increased but then showed a minor downward trend.…”
Section: Epoxy Resin Systemsmentioning
confidence: 99%
“…There are important criteria for these feedstock, for example, low density, strength properties, flexibility and cost effectiveness are the main criteria for using wood powder in composite products [120]. The binding agents of wood powder composites are adhesive i.e., UF (urea formaldehyde) [117,[121][122][123][124][125], epoxy-resin [126], PF (phenol formaldehyde) [127,128]; thermoplastic i.e., polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyethylene-terephthalate [108,113,118,120,[129][130][131][132][133][134][135][136][137][138][139][140][141]; natural adhesive [142,143] and Portland cement [144][145][146][147][148][149][150][151]. There is no need for binding agents in particleboards from wood powder [152].…”
Section: Raw Materials For Compositesmentioning
confidence: 99%
“…When all of the eucalyptus fiber was replaced (Sample 4), the strain of the composite was much higher. The short-term creep performance of the ternary composites was improved with a proper amount of lignin, and then declined with excess lignin (Durán et al 2016;He et al 2016;Dörrstein et al 2018).…”
Section: Physical and Mechanical Properties Of The Compositesmentioning
confidence: 99%